Ferromagnetism: Epitaxial Growth of Intermetallic MnPt Films on Oxides and Large Exchange Bias (Adv. Mater. 1/2016). Issue 1 (January 2016) - Liu, Zhiqi; Biegalski, Michael D.; Hsu, Shang‐Lin; Shang, Shunli; Marker, Cassie; Liu, Jian; Li, Li; Fan, Lisha; Meyer, Tricia L.; Wong, Anthony T.; Nichols, John A.; Chen, Deyang; et al.
Abstract : On page 118, Z. Q. Liu, H. M. Christen, and co‐workers demonstrate epitaxial growth of intermetallic MnPt on oxides, promising for magnetoelectric applications. In high‐quality films, large exchange coupling between this antiferromagnet and a ferromagnetic layer is observed. In contrast, Mn/Pt antisites result in ferromagnetism, despite the robustness of the antiferromagnetism in bulk MnPt. Image credit: Changjian Li, NUS.